Intrafamilial Characteristics Are Important Predictors of Children's Diets in New Mexico's Border Colonias. Issue 6 (November 2022) - McDonald, Jill A.; Sroka, Christopher J.; Olivares, Elizabeth; Marin, Merranda R.; Gurrola, Maria; Sharkey, Joseph R.
Introduction: We assessed selected nutritional indicators in Mexican-origin children in two low-income, rural colonias in New Mexico on the U.S.–Mexico border. These children are at higher risk for obesity and other chronic diseases linked to poor nutrition in childhood, but little is known about their diets. Method: We surveyed mothers of 202 children 6 to 10 years old about sociodemographic characteristics, family and child attitudes and behaviors, and the child's diet. We compared diet with dietary recommendations and used regression trees to identify significant predictors of recommended intake. Results: Among families, 89.1% participated in Medicaid, and 52.5% participated in a Supplemental Nutrition Program. More children met recommendations for fruit (36.1%) than vegetables (1.5%). Greater vegetable intake was associated with a child's not thinking healthy food tasted bad, greater family activity, and younger maternal age. Only 5.0% of children met the recommendation for <10% of energy from added sugar, with the average child consuming 2.4 times that from sugar-sweetened beverages and snacks. Lower sugar intake was associated with less screen time, not having TV on during meals, and playing team sports. Family access to healthy food and child use of mobile food vendors, vending and convenience stores were not predictive of diet. Conclusion: Hispanic children in border colonias have poor diets that put them at risk for obesity and numerous chronic diseases. Addressing this problem will require changing family norms and attitudes toward healthy food, screen time behavior, and physical activity levels within families.